The viable system perspective of actors in eco-systems. Issue 6 (9th October 2017) - Polese, Francesco; Carrubbo, Luca; Bruni, Roberto; Maione, Gennaro
Abstract : Purpose: The purpose of this paper is to show the relevance of the interest in sharing the common purpose and in searching for a common survival of emerging eco-system (ES) as an entity that "is not" but emerges by the viable actors interaction. Design/methodology/approach: This conceptual paper contributes to the research by defining the ES building on the contributions of SD logic and viable systems approach (VSA), with a particular focus on the VSA perspective. Findings: An ES emerges as a viable "system of systems" by an observer's interpretation of the simultaneous interactions between different viable actors/systems that are sharing a common purpose (the survival of the ES), exchanging resources following a viable value co-creation model. Each actor/system could represent a level of quality of belonging to the ES looking for the opportunity to be resonant with the ES. Research limitations/implications: The ES features and the role of each actor inside could be deepened through different theoretical perspectives and the same VSA to the ES could be reached with empirical explorations. Practical implications: Understanding the nature of the ES, the practitioners are able to explain better their position in relation to partners and competitors. It is possible to be a part of several emerging ESs looking for the will to contribute to the ES' survival and to the sharing of the purpose of the interactive systems/actors. In a medium and long run, the measure of the resonance is useful to understand the quality in interaction. Originality/value: The work provides a definition of the ES and the actors inside focusing on the perspective of VSA, by integrating the concept of viable value co-creation and solidarity-based logic; in particular, the concept of Centro Commerciale Naturale is used to show the emergence of the ES in a relational context generated by the interaction between city, service and retailers in a city center.